(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
In early childhood education, English language learners face a multitude of challenges that are unique to their educational experience. One challenge is English literacy, a required skill for later academic achievement. Contemporary research efforts have examined various pedagogical approaches that address these issues, such as culturally responsive teaching. This manuscript explores literacy methodologies through the lens of culturally responsive teaching, which include connecting cultural values between school and home through parental involvement, encouraging high self-efficacy in early childhood educators of ELLs, using evidence-based instructional methods, and connecting other languages with English to promote second language acquisition. Such efforts are important because appropriate support for English language learners is necessary to promote educational equity within the United States education system.